A comparison of the cyclic voltammetry of the Sn/Sn(II) couple in the room temperature ionic liquids N-butyl-N-methylpyrrolidinium dicyanamide and N-butyl-N-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide: solvent induced changes of electrode reaction mechanism. - Martindale, B; Ward Jones, SE; Compton, R (2010)
The Sn/Sn(II) couple is studied in the room temperature ionic liquids N-butyl-N-methylpyrrolidinium dicyanamide, [C(4)mpyrr][N(CN)(2)] and N-butyl-N-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide, [C(4)mpyrr][NTf(2)] using cyclic voltammetry. The Sn(II) species is introduced into each of the ionic liquids by dissolving either SnCl(2) or Sn(CF(3)SO(3))(2). The diffusion coefficient of the Sn(II) species produced is found to vary with the ionic liquid, partly reflecting the difference in the viscosity of the two liquids, but also to vary with the Sn(II) salts used, indicating that different Sn(II) species may be present. The mechanism for the stripping of deposited tin is found to change with potential and also vary with the Sn(II) salt/ionic liquid combination used. In [C(4)mpyrr][N(CN)(2)] the mechanism for the tin stripping process is broadly similar for both of the Sn(II) salts used indicating that the morphology of the tin deposit is similar and that the stripping mechanism is largely independent of the Sn(II) salt anion. In [C(4)mpyrr][NTf(2)] a large difference was seen in the voltammetry of the different Sn(II) salts. Tafel analysis is used to show that the mechanism of the oxidation of Sn is sensitive to the solvent, the salt and the potential. The rate determining step was found to vary between the first electron transfer, the second electron transfer and a step likely involving reactions of a Sn(+) intermediate.